2017
DOI: 10.1111/jfb.13314
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for long‐term change in length, mass and migration phenology of anadromous spawners in French Atlantic salmon Salmo salar

Abstract: This study provides new data on Atlantic salmon Salmo salar life-history traits across France. Using a long-term recreational angling database (1987-2013) covering 34 rivers in three regions (genetic units), a decline in individual length, mass and a delayed adult return to French rivers was reported. Temporal similarities in trait variations between regions may be attributed to common change in environmental conditions at sea. The relative rate of change in phenotypic traits was more pronounced in early matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
18
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 78 publications
(149 reference statements)
7
18
0
4
Order By: Relevance
“…That multi‐decadal shifts in the size and age of returning fish have occurred in many North Atlantic salmon stocks is unequivocal (Bacon et al ., ; Bal et al ., ; Jonsson et al ., ; Olmos et al ., ; Quinn et al ., ; Todd et al ., , ). On average, individuals are returning smaller and, in many cases, younger.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…That multi‐decadal shifts in the size and age of returning fish have occurred in many North Atlantic salmon stocks is unequivocal (Bacon et al ., ; Bal et al ., ; Jonsson et al ., ; Olmos et al ., ; Quinn et al ., ; Todd et al ., , ). On average, individuals are returning smaller and, in many cases, younger.…”
Section: Discussionmentioning
confidence: 98%
“…The primary aim of the analysis was to develop a robust predictive model that could be used to estimate egg numbers from biological characteristics of female salmon where direct measures of fecundity are absent; i.e ., the majority of populations in Scotland. The need to make quantitative assessments of multiple populations, based on a limited amount of empirical data from a proportion of those populations, is a common challenge in wildlife management and one for which Bayesian hierarchical modelling is particularly suited (Bal et al ., ; Massiot‐Granier et al ., ; Prévost et al ., ). By adopting a hierarchical modelling approach, the models were allowed to pool information common to observations from the same river or year, and to respond to variation among these clusters.…”
Section: Methodsmentioning
confidence: 99%
“…Hierbij is de aanname gedaan dat alle gevangen zalmen boven de 1,5 kg stroomopwaarts migrerende dieren zijn. Deze 1,5 kg is gebaseerd op studies van Bacon et al (2006) en Bal et al (2017) die het gemiddelde gewicht per jaar van intrekkende zalmen hebben gemeten. In de studie van Bacon et al (2006) Bij de enquêtes is gevraagd om bijgevangen zalmen in te delen in drie lengteklassen (<25 cm, 25-50 cm, >50 cm).…”
Section: Commerciële Visserijunclassified
“…In addition to reductions in overall abundance, some studies have also identified long-term declines in adult body size (e.g. Bal et al, 2017;Bielak & Power, 1986;Jonsson, Jonsson & Albretsen, 2016;Quinn, McGinnity & Cross, 2006), where smaller size at maturity is attributed to lower marine growth rates (Jonsson & Jonsson, 2004). The body size of salmonids is an important characteristic, frequently linked to their reproductive success (Dickerson, Quinn & Willson, 2002).…”
mentioning
confidence: 99%
“…Previous studies investigating long-term trends in the size of Atlantic salmon are underpinned by data from commercial netting stations (Bacon et al, 2009;Todd et al, 2008) or rod-and-line fisheries in large or multiple river systems and represent multiple populations and stocks (Bal et al, 2017;Bielak & Power, 1986;Quinn et al, 2006). The analysis and interpretation of such data can be challenging because the average length and weight of salmon returning to the coast increases with day of the year (Bacon et al, 2009), and stock components with different biological characteristics migrate at different times of year (Stewart, Smith & Youngson, 2002), so trends in size might be confounded with changes in sampling date and run timing.…”
mentioning
confidence: 99%